Nietzsche's Concept of Health - Ian D Dunkle (Ergo, An Open Access Journal of Philosophy, 2022)
Nietzsche assesses values, moralities, religions, cultures, and persons in terms of health. He argues that we should reject those that are unhealthy and develop healthier alternatives. But what is Nietzsche’s conception of health, and why should it carry such normative force? In this paper I argue for reading Nietzsche’s concept of health as the overall ability to meet the demands of one’s motivational landscape. I show that, unlike other interpretations, this reading accounts for his rejection of particular features of a prevailing, then as now, model of health; for his association of health with strength and with psychic unity; and for his claim that health is compatible with, and can even be enhanced by, functional impairments such as those from which he personally suffered. Throughout I draw connections to recent literature on health and disability.